Abnormal N-glycosylation pattern for brain nucleotide pyrophosphatase-5 (NPP-5) in Mecp2-mutant murine models of Rett syndrome. (April 2016) - Cortelazzo, Alessio; De Felice, Claudio; Guerranti, Roberto; Signorini, Cinzia; Leoncini, Silvia; Pecorelli, Alessandra; Scalabrì, Francesco; Madonna, Michele; Filosa, Stefania; Della Giovampaola, Cinzia; Capone, Antonietta; Durand, Thierry; et al.
Highlights: Brain NPP-5 N -glycosylation was investigated in Mecp2 mutant Rett mouse models. Decreased NPP-5 N -glycosylation is evidenced in presymptomatic and symptomatic mice. NPP-5 glycosylation changes are rescued by Mecp2 gene reactivation in the brain. A causal link between the amount of Mecp2 and NPP-5 N -glycosylation was evidenced. Abstract: Neurological disorders can be associated with protein glycosylation abnormalities. Rett syndrome is a devastating genetic brain disorder, mainly caused by de novo loss-of-function mutations in the methyl-CpG binding protein 2 ( MECP2 ) gene. Although its pathogenesis appears to be closely associated with a redox imbalance, no information on glycosylation is available. Glycoprotein detection strategies (i.e., lectin-blotting) were applied to identify target glycosylation changes in the whole brain of Mecp2 mutant murine models of the disease. Remarkable glycosylation pattern changes for a peculiar 50 kDa protein, i.e., the N -linked brain nucleotide pyrophosphatase-5 were evidenced, with decreased N -glycosylation in the presymptomatic and symptomatic mutant mice. Glycosylation changes were rescued by selected brain Mecp2 reactivation. Our findings indicate that there is a causal link between the amount of Mecp2 and the N -glycosylation of NPP-5.